Cultural value as the basis for the microfinance development of the Farmer’s Group Association - Bernard Edheney Huruta; Yulius Pratomo (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This study aims to describe the form of local wisdom (cultural value) in rural microfinance — this study conducted from October until December 2018 in Wangga Village, East Sumba. A qualitative method was used to picture the phenomenon of local wisdom-based microfinance development in communities. The authors used in-depth interviews with eight informants from the Rinjung Pahamu Farmer’s Group Association. The eight informants were determined purposively. Also, the data collection was carried out through a focus group discussion with the Rinjung Pahamu Farmer’s Group Association. The results of the study show that the local wisdom experienced by the members of the Rinjung Pahamu Farmer’s Group Association was used to overcome the limited access to formal financial services. The forms of microfinance developed on the Island of Sumba could not be separated from the appreciation of the noble values (Marapu) adopted by the community, such as the philosophy of Pawandang, Hillu Kandutuku, and Rotu Padang. Furthermore, savings and loan activities carried out in the management of the Farmer’s Group Association always consider the aspects of justice and survival. Based on the successful experience of the Rinjung Pahamu Farmer’s Group Association, in the future, the cultural value as the basis for the microfinance development can be applied to other groups as a means to improve financial access among the poor, especially for those living in rural areas. Marapu’s belief that was adopted by the people in Wangga Village still used as the basis for carrying out various activities in people’s lives. Marapu’s view is the belief that the government acknowledges pride, and it strengthens the community to maintain survival and balance. It practised through the Pawandang, Hillu Kandutuku, and Rotu Padang activities.